Diastereoselective and enantioselective photoredox pinacol coupling promoted by titanium complexes with a red-absorbing organic dye. Issue 20 (4th May 2022) - Calogero, Francesco; Magagnano, Giandomenico; Potenti, Simone; Pasca, Francesco; Fermi, Andrea; Gualandi, Andrea; Ceroni, Paola; Bergamini, Giacomo; Cozzi, Pier Giorgio
Abstract : A metallaphotoredox, diastereoselective and enantioselective pinacol coupling reaction promoted by titanium complexes with the use of a red-absorbing organic dye was developed. Abstract : The pinacol coupling reaction, a reductive coupling of carbonyl compounds that proceeds through the formation of ketyl radicals in the presence of an electron donor, affords the corresponding 1, 2-diols in one single step. The photoredox version of this transformation has been accomplished using different organic dyes or photoactive metal complexes in the presence of sacrificial donors such as tertiary amines or Hantzsch's ester. Normally, the homo-coupling of such reactive ketyl radicals is neither diastereo- nor enantio-selective. Herein, we report a highly diastereoselective pinacol coupling reaction of aromatic aldehydes promoted by 5 mol% of the non-toxic, inexpensive and available Cp2 TiCl2 complex. The key feature that allows the complete control of diastereoselectivity is the employment of a red-absorbing organic dye in the presence of a redox-active titanium complex. Taking advantage of the well-tailored photoredox potential of this organic dye, the selective reduction of Ti(iv ) to Ti(iii ) is achieved. These conditions enable the formation of the d, l ( syn ) diastereoisomer as the favored product of the pinacol coupling (d.r. > 20 : 1 in most of the cases). Moreover, employing a simply prepared chiral SalenTi complex, the new photoredox reaction gave a complete diastereoselection for the d, l diastereoisomer, and high enantiocontrol (up to 92% of enantiomeric excess).